Mapping Surface Potential in DNA Aptamer–Neurochemical and Membrane–Ion Interactions on the SOS Substrate Using Terahertz Microscopy - Kosei Morita; Yuta Mitsuda; Sota Yoshida; Toshihiko Kiwa; Jin Wang (Biosensors)
In this study, we utilized a terahertz chemical microscope (TCM) to map surface potential changes induced by molecular interactions on silicon-on-sapphire (SOS) substrates. By functionalizing the SOS substrate with DNA aptamers and an ion-selective membrane, we successfully detected and visualized aptamer–neurochemical complexes through the terahertz amplitude. Additionally, comparative studies of DNA aptamers in PBS buffer and artificial cerebrospinal fluid (aCSF) were performed by computational structure modeling and terahertz measurements. Beyond neurochemicals, we also investigated calcium ions, measuring their concentrations in PDMS-fabricated micro-wells using minimal sample volumes. Our results highlight the capability of TCM as a powerful, label-free, and sensitive platform for the probing and mapping of surface potential arising from molecular interactions, with broad implications for biomedical diagnostics and research.